3D printing of anisotropic polymer nanocomposites with aligned BaTiO3 nanowires for enhanced energy density. Issue 1 (3rd April 2020) - Luo, Hang; Zhou, Xuefan; Guo, Ru; Yuan, Xi; Chen, Hehao; Abrahams, Isaac; Zhang, Dou
Abstract : High-performance flexible poly(vinylidene fluoride–chlorotrifluoroethylene) (P(VDF–CTFE)) nanocomposites with aligned BaTiO3 nanowires using 3D printing technology were demonstrated. Abstract : High power density capacitors possess broad application prospects in electric vehicles and power transmission systems. The development of capacitors with high energy density to realize miniaturization and lightweight application is the bottle-neck in this field. Strategies including orientated distribution of fillers have been utilized to increase the energy density of the dielectrics. In this work, we demonstrate high-performance flexible poly(vinylidene fluoride–chlorotrifluoroethylene) (P(VDF–CTFE)) nanocomposites with aligned BaTiO3 nanowires using 3D printing technology. The 3D printing process is computer-controlled, which can effectively achieve designed geometric shapes and precise size. The resulting BaTiO3 nanowires are highly aligned in a direction parallel to the surface of the nanocomposites due to the high shear environment within the very small 100 μm diameter nozzle. The highest energy density for these nanocomposites, with aligned BaTiO3 nanowires, was 14.52 J cm −3, which is 55% higher than that of nanocomposites with random BaTiO3 nanowires at the same loading level. This facile and readily scalable method of aligning one-dimensional fillers in a polymer matrix has potential not only in dielectric capacitor technology, but also in other fields where directional arrangement of low dimensional nanostructured materials is needed.